Wind energy and energy potential assessment on Ambon Island - Lory Marcus Parera; Abhi Rizky Heluth; Mey Chintya Yesaya; Johanis Leuwol (Bulletin of Electrical Engineering and Informatics, 2026)
Ambon Island has a high dependence on fossil fuels, which causes environmental and energy security problems, even though the potential for renewable energy, especially wind, is enormous according to national energy plan data. This study aims to assess the technical and economic feasibility of wind energy development in Latuhalat Village as a case study. Wind speed and direction data for the period January-December 2024 from the Ambon Maritime Meteorological Station were analyzed, showing that the prevailing winds are from the east and southeast. Assuming an air density of 1.225 kg/m³, a turbine efficiency of 35%, and a rotor sweep area of 78.54 m², the estimated annual energy reaches 24,528 kWh. A capacity factor of 30% results in a realistic output of 7,358 kWh/year. A horizontal-axis wind turbine with inverse taper blades is recommended to suit local wind characteristics, producing 0.7-46.8 kW of power with a system efficiency of 67%. This study concludes that Latuhalat Village has viable wind energy potential for further development. Its implementation requires a holistic approach encompassing technical, economic, social, and policy aspects to support sustainable energy transition on Ambon Island.